Study on sound absorbing mechanism of MPP affected by bending resonance of panel. Issue 4 (2017) - Kamada, Yoshinobu; Kashiwao, Tomoaki; Hoshino, Shuto; Shimada, Takafumi
Followed by the study (Sakagami et al., 2010a) about the micro-perforated panel (MPP) with honeycomb structure, in this paper, the MPP for vehicle noise, vibration and harshness (NVH) performance development is studied, where the MPP prototype is moulded by a sophisticated 3D printer, and its sound absorption coefficients are measured by the experiment of acoustic impedance tube. Two proposals are made according to the interpretation of absorbing mechanism. One is the potentiality of thin MPP not combined but contacted with honeycomb core, which might cause higher sound absorption by the induced sound impact effect. The other is the potentiality of 3D-MPP that increases the design parameters by the mass and the depth of aperture as well as the diameter and the pitch among apertures.